The problem of mathematical finite element modeling of inhomogeneous deformable solids using scanning - V. L. Duong (Advanced Engineering Research, 2019)
Introduction. In the mathematical finite element modeling, an average value of the mechanical characteristics of the deformable solid material is used. In aircraft, machine building, construction engineering, medicine and other fields, polymer composite materials and materials of natural origin are increasingly used. In the latter case, the actual change in the mechanical characteristics differs significantly from the averaged change; therefore, when using the averaged parameters to build and analyze finite element models, the results can be significantly distorted. This paper describes the creation of mathematical methods for studying changes in the mechanical characteristics of a material of inhomogeneous deformable solids. The results obtained in this way are used to construct finite element models and analyze their stress-strain state.Materials and Methods. Naturally occurring materials and composites are considered as inhomogeneous deformable solids. To study the changes in the mechanical characteristics of the material, a method was developed based on the use of two components: the pixel characteristics of raster images scanned by a computer tomograph and the experimental data of field tests of standard samples.Research Results. A complex of mathematical methods has been developed for modeling the interpretation of scanning raster images by a computer tomograph, which allows for the study of any complicated structures of real deformable solids. The results are used in the construction of finite element models of such bodies considering the heterogeneity of the mechanical characteristics of the material. The analysis of the stress-strain state of finite element models of test samples has proved the accuracy and convergence of the numerical solution of the finite element method in modeling the property of heterogeneity of the mechanical characteristics of the material.Discussion and Conclusions. The developed approach can be applied to any physical principles of scanning (X-ray, ultrasound, laser, etc.) and for any types of materials if the data obtained as a result of scanning is developed in the form of a digital (raster) image.